KAJIAN KERUSAKAN MATERIAL SUPERHEATER TUBE 2” DENGAN PENDEKATAN STANDAR ASTM - Koos Sardjono Kuntadi (JURNAL STANDARDISASI, 2006)
Equipments used in industry process and migas is generally designed from alloy of steel which hold up to high temperature and attack corrosion. Based on that, it’s require to be conducted an material operation and election, like a component Boiler that is Secondary Superheater is generally weared by pipe from alloy of steel material Cr- Mo or steel with Austenitik type.To know the damage of Secondary Superheater tube 2" material, can be conducted by a chemical composition analysis, test inspection metalografi and hardness. The damage of Material Secondary Superheater tube 2" at the extension las elbow in the form of rip on second potition (ASTM SA - 192) representing a militant low strength carbon material pipe, while on the first potition which there are not pipe material damage representing a militant high strength carbon (ASTM SA - 106 grade C) which a different thick each other. Attenuating showed the thick degradation which possible because of local stream turbulensi warm-up existence and which is high enough, this matter is shown with existence